Journey to Newland : - Poole, Bill (Pfeiffer/John Wiley, 2007)
The Journey to Newland Participant Workbook provides workshop participants with a road map for navigating the change journey from start to finish. This comprehensive framework -- with its easy-to-follow process, memorable methodologies, and practical tools -- enables participants to explore and eventually master the skills that are most crucial to transformational change? leading change, building teams, valuing differences, and optimizing communication. Using this handy Workbook, in conjunction with a workshop, will help leaders simplify complex issues and bring intangible concepts down to earth. Participants will meet and become familiar with a cast of memorable characters, engage in a captivating story, and learn a common language to deal with emotionally sensitive issues.